2014
DOI: 10.1111/edt.12101
|View full text |Cite
|
Sign up to set email alerts
|

Using rigidly fixed autogenous tooth graft to repair bone defect: an animal model

Abstract: Rigid fixation of autogenous tooth could serve as a novel approach for the repair of bone defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…In large bone defects where a significant amount of the bony tissue has been lost, a direct injection method has been found to be ineffective for MSC delivery and the acceleration of the bone healing process [Qin et al, 2014a]. Recently, it has been suggested that the controlled delivery of MSCs and factors that promote healing within biomaterial carriers (hydrogel, scaffold, etc.)…”
Section: Tissue Engineering Approachesmentioning
confidence: 99%
“…In large bone defects where a significant amount of the bony tissue has been lost, a direct injection method has been found to be ineffective for MSC delivery and the acceleration of the bone healing process [Qin et al, 2014a]. Recently, it has been suggested that the controlled delivery of MSCs and factors that promote healing within biomaterial carriers (hydrogel, scaffold, etc.)…”
Section: Tissue Engineering Approachesmentioning
confidence: 99%
“…, Qin et al. ). Moreover, intentionally retained buccal root fragments also supported the osseointegration process by a new cementum formation (Hürzeler et al.…”
mentioning
confidence: 99%
“…[232425] Furthermore, the use of porous dentin scaffolds supports rapid microvascular ingrowth, as well as osseointegration, in mice, highlighting their potential as bone engineering materials. [26]…”
Section: Discussionmentioning
confidence: 99%